Economic conditions in Bosnia and Herzegovina during the World War One - Užičanin, Salkan (Historical Thought, 2025)
The World War I (WWI) caused the major disturbance in the economic life of Bosnia and Herzegovina. Special difficulties to the economy were created by the militarization of certain number of enterprises, mobilization of the work force population, as well as the unscrupulous requisition. Besides the above mentioned, the economy coped with transportation difficulties, a number of taxation levies, losses of business connections, lack of loans, etc. Consequences of all of that were the downsizing and lull of the production in the economic branches which did not operate for the military needs, which in turn resulted not only in war destruction and devastation, but also in major economical losses.